Notes on patriarchy in the Palanca Award winning short stories in Cebuano - Bañez, Helen V. (2001)
This study attempts to examine the extent to which the patriarchal system has permeated the writing of short stories in Cebuano, especially in the Palanca awardwinning short stories. These stories are discussed as a reflection of the patriarchal nature of Cebuano society.
Keywords: Carlos Palanca Memorial Awards for Literature; Short stories -- Cebuano language